The Impact of Leadership and Competence on the Effectiveness of Village Fund Management in Walea Kepulauan Subdistrict, Tojo Una-Una District - Hamsa, Ma’mun; Natsir, Nawawi; Haryono, Dandan (Lafadz Jaya Publisher, 2025)
This study aims to investigate the influence of leadership and competence on the effectiveness of village fund management in Walea Kepulauan Subdistrict, Tojo Una-Una District. The specific objectives are: (1) to examine the effect of village head leadership on the effectiveness of village funds, (2) to explore the impact of village apparatus competence on the effectiveness of village funds, and (3) to analyze the simultaneous influence of both village head leadership and apparatus competence on the effectiveness of village funds. The research utilizes a survey approach with a quantitative method. A total of 117 respondents, including village government officials and members of the Village Consultative Body (BPD), were selected from Walea Kepulauan Subdistrict. Data analysis was conducted using multiple regression analysis with the assistance of SPSS software. The results show that: (1) village head leadership has a negative and significant effect on the effectiveness of village funds, contributing 11.9%, (2) village apparatus competence has a positive and significant effect on the effectiveness of village funds, contributing 45.6%, and (3) both village head leadership and apparatus competence together have a positive and significant effect on the effectiveness of village funds, contributing 51.2%. These findings suggest that enhancing leadership quality and the competence of village apparatuses is crucial for improving the management and effectiveness of village funds in Walea Kepulauan Subdistrict.